2014
DOI: 10.1021/jz401961j
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Dynamics of Interfacial Water by Free Induction Decay Sum Frequency Generation (FID-SFG) at the Al2O3(1120)/H2O Interface

Abstract: The dephasing dynamics of a vibrational coherence may reveal the interactions of chemical functional groups with their environment. To investigate this process at a surface, we employ free induction decay sum frequency generation (FID-SFG) to measure the time that it takes for free OH stretch oscillators at the charged (pH ≈ 13, KOH) interface of alumina/water (Al2O3/H2O) to lose their collective coherence. By employing noncollinear optical parametric amplification (NOPA) technology and nonlinear vibrational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 37 publications
2
37
0
1
Order By: Relevance
“…The interpretation of the small differences in shape and area of the -OH signal at 150 and 250 C is not straightforward and beyond the scope of this work. 42 Replacing TMA with a fully deuterated molecule [D-TMA, Al(CD 3 ) 3 ] should lead to a shift of the stretch mode of the -CH 3 groups by a factor of $ ffiffi ffi 2 p toward lower wavenumbers. Figure 10 shows the signal of the C-D stretch mode of the -CD 3 groups which was detected at 2125 cm À1 which is indeed shifted by a factor of $ ffiffi ffi 2 p compared to stretch mode of -CH 3 at 2890 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…The interpretation of the small differences in shape and area of the -OH signal at 150 and 250 C is not straightforward and beyond the scope of this work. 42 Replacing TMA with a fully deuterated molecule [D-TMA, Al(CD 3 ) 3 ] should lead to a shift of the stretch mode of the -CH 3 groups by a factor of $ ffiffi ffi 2 p toward lower wavenumbers. Figure 10 shows the signal of the C-D stretch mode of the -CD 3 groups which was detected at 2125 cm À1 which is indeed shifted by a factor of $ ffiffi ffi 2 p compared to stretch mode of -CH 3 at 2890 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…For the (11true2 0) interface in contact with water, the frequency of the dangling OH group of Al 2 OH has been reported to be similar to that of the (0001) interface [44] . A free induction decay study [45] on the (1120) surface provides indications that this free‐OH stretch mode might consist of two modes centered at 3644, assigned to aluminum hydroxy groups, and 3679 cm −1 , attributed to a free‐OH stretch of interfacial water, with dephasing times of about 90 and 900 fs, respectively. The SFG response of the interfacial water molecules at about 3200 and 3400 cm −1 at this (11true2 0) interface is sensitive to the pH value, with a minimum in the SFG intensity around pH 6.7 [44] .…”
Section: Aluminamentioning
confidence: 95%
“…[18][19][20] Likewise, nonlinear optical measurements have revealed that halide and alkali ions influence silanol group dissociation at silica/water interfaces, [21][22][23] a result that perhaps is linked to reports that certain alkali chlorides at high ionic strengths enhance silica dissolution rates. 18,[24][25][26][27][28] Perturbations to the hydrogen-bonded network Page 3 of interfacial water molecules 29 and a considerable lengthening of the T2 relaxation time of interfacial water molecules with certain ions at elevated ionic strength [30][31][32] have been reported as well. We now investigate how a series of alkali halides interact with the fused silica/water interface at concentrations ranging from 10 µM to 0.1 M at circumneutral pH.…”
mentioning
confidence: 93%